Optimal modes of mind-body exercise for treating chronic non-specific low back pain: Systematic review and network meta-analysis - Shi, Jian; Hu, Zheng-Yu; Wen, Yu-Rong; Wang, Ya-Fei; Lin, Yang-Yang; Zhao, Hao-Zhi; Lin, You-Tian; Wang, Yu-Ling (Frontiers in Neuroscience, 2022)
Background There were limited studies that directly compare the outcomes of various mind-body exercise (MBE) therapies on chronic non-specific low back pain (CNLBP). Objectives To compare the efficacy of the four most popular MBE modes [Pilates, Yoga, Tai Chi (TC), and Qigong] in clinically CNLBP patients, we conducted a systematic review and network meta-analysis (NMA). Methods We searched databases for eligible randomized controlled trials (RCTs) (from origin to July 2022). RCTs were eligible if they included adults with CNLBP, and implemented one or more MBE intervention arms using Pilates, yoga, TC, and qigong. In addition, pain intensity and physical function were evaluated using validated questionnaires. Results NMA was carried out on 36 eligible RCTs involving 3,050 participants. The effect of exercise therapy on pain was in the following rankings: Pilates [Surface under cumulative ranking (SUCRA) = 86.6%], TC (SUCRA = 77.2%), yoga (SUCRA = 67.6%), and qigong (SUCRA = 64.6%). The effect of exercise therapy on function: Pilates (SUCRA = 98.4%), qigong (SUCRA = 61.6%,), TC (SUCRA = 59.5%) and yoga (SUCRA = 59.0%). Conclusion Our NMA shows that Pilates might be the best MBE therapy for CNLBP in pain intensity and physical function. TC is second only to Pilates in improving pain in patients with CNLBP and has the value of promotion. In the future, we need more high-quality, long-term follow-up RCTs to confirm our findings. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=306905, identifier: CRD42022306905.